Evaluasi Program Indonesia Pintar Sebagai Kebijakan Peningkatan Kesetaraan Pendidikan Dan Kurikulum - Jeffry Sony Junius Lengkong; Suiling Pontoh; Maria Kaparang; Victor Nomel Kumajas (Departement of Mathematics Education, 2024)
This research aims to evaluate the Smart Indonesia Program (PIP) as a policy to increase educational and curriculum equality. This research uses qualitative methods with library study techniques based on data all sourced from national journal databases. At the same time, appropriate search terms are a prerequisite for accurate data acquisition. To make search results as comprehensive and accurate as possible, the Authorb of Science core collection was selected for this study. This research uses the subject